Neurofibromatosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
LINK (Let's Increase Neurofibromatosis Knowledge), the British Neurofibromatosis Association, organised a major European Symposium at Egham, Surrey, Feb 5-7, 1987, and clarified the distinguishing features of two syndromes with separate genetic markers: 1) von Recklinghausen's neurofibromatosis (VRNF), the so-called peripheral type, and 2) bilateral acoustic neurofibromatosis (BANF), the central variety.